Design and Development of an Employee Attendance and Performance Evaluation Application Based on Mobile and Web with Face Recognition, Geolocation, and the SAW Method at Toll Road Company PT XYZ - Krisna Restu Dewanta; Ahmad Habib (Soegijapranata Catholic University, 2026)
This research aims to design a mobile-based attendance app for the toll road company in East Java, PT XYZ.Using Face Recognition and Geolocation to simplify employee attendance. The app features an employee performance evaluation system based on the Simple Additive Weighting (SAW) method via a web admin interface. Employees can clock in using real-time facial recognition and location validation, while admins can monitor attendance and performance. Developed using Extreme Programming (XP) and tested through User Acceptance Testing (UAT), the app enhances efficiency, accuracy, and transparency in managing attendance and performance across multiple locations.